PROBLEMATIKA EKONOMI DALAM ISLAM - Lubis, Fahmi Husaini; Syahriza, Rahmi; Tarigan, Azhari Akmal (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
Abstrack This research aims to determine the dynamics and problems of sharia economics in Islamic countries. In writing about the dynamics and problems of sharia economics in Muslim countries, the analytical method used is library research. And what is used as primary data in this research is data obtained directly from the main source, namely literature that discusses the dynamics and problems of sharia economics in Muslim countries. The results of this paper show that the dynamics of sharia economics in Muslim countries began with the emergence of sharia economic institutions which then continued to develop from time to time. And the problems with sharia economics in Muslim countries are the lack of human resources, the low level of understanding and concern among the people and the lack of public services. Solutions in dealing with Islamic economic problems include the correlation of educational institutions in the development of sharia economics, attention from the government, showing the real role of sharia economics. Improving the quality of less competent and professional human resources, training/education/socialization to employees and the community, innovative marketing, product innovation, reorientation to the real sector and improving service and professionalism